LiDAR-based Computational Fluid Dynamics heat transfer models for bushfire conditions. (December 2021) - Hendawitharana, Sahani; Ariyanayagam, Anthony; Mahendran, Mahen; Gonzalez, Felipe
Abstract: Post-bushfire damage assessments show no significant reduction in property damage when compared with past bushfire events. Other than the severity of the attack and the behaviour of the bushfires, the architectural design of the houses, construction materials and, many other factors affect bushfire house ignition. These are generally ignored in the simulations using simplified models. An improved bushfire risk assessment can be conducted if the exact surrounding and the architectural design of the existing houses are considered. However, this is not widely practised due to associated high cost and time, which can be minimised by the adaptation of modern technologies in an efficient way. This study proposes a novel approach to assess the effect of bushfires on individual building structures (houses) in bushfire-prone areas, through heat transfer modelling. It utilises ground and airborne Light Detection and Ranging (LiDAR) point cloud to model individual building structures with all their complex features and the surroundings with good dimensional accuracy. These point cloud maps were used to develop heat transfer models by using Fire Dynamics Simulator (FDS) to investigate wind velocities, temperature profiles and pressure distributions during bushfires. A case study was conducted for a selected house (elevated building structure) using the proposed approach and the results were compared against a simplified cuboid model of the same house. The simulation results show that the proposed approach is capable of identifying the most vulnerable locations of the building structure compared to the simplified model, which emphasises its applicability in bushfire planning and damage mitigation.